Development of reaction kinetics model for the production of synthesis gas from dry methane reforming - Inayat, A. (Diponegoro University, 2021)
The energy supply systems dependent on fossils and municipal solid waste (MSW) materials are primarily responsible for releasing greenhouse (GHG) gases and their related environmental hazards. The increasing amount of methane (CH4) and carbon dioxide (CO2) is the scientific community's main concern in this context. Reduction in the emission amount of both gases combined with the conversion technologies that would convert these total threat gases (CO2 and CH4) into valuable feedstocks will significantly lower their hazardous impact on climate change. The conversion technique known as dry methane reforming (DMR) utilizes CO2 and CH4 to produce a combustible gas mixture (CO+H2), popularly known as synthesis gas/or syngas. Therefore, this research study aims to explore and enlighten the characteristics of the DMR mechanism. The conversion behaviour of CO2 and CH4 was studied with modelling and simulation of the DMR process using MATLAB. The results showed that inlet gas flow has a significant impact on the reactions. In contrast, the inlet molar composition ratio of the reactions was found to have no substantial effect on the mechanism of DMR. Copyright Â© 2021 by Authors, Published by BCREC Group.